EARLY COMPLICATIONS OF ACUTE MYOCARDIAL INFARCTION WITH ST SEGMENT ELEVATION - N.U., Ibragimova; S.S., Mavlonberdiyev; Sh. M., Aripov; G. Oʼ., Tuyimova (PT. Antis International Publisher, 2024)
Myocardial infarction is a dangerous disease that causes irreversible changes in the heart. The disease mainly occurs in people over 50 years of age. According to statistics, in general, about 60% of people over the age of 65 have experienced a heart attack. However, younger people are also at risk of the disease. Assess the true natural history of acute myocardial infarction is difficult for a number of reasons: the possibility of hidden infarction, the high frequency of acute coronary death outside the hospital and the difference methods for diagnosing this condition.